STRATEGI PENGEMBANGAN AGRIBISNIS TEMBAKAU DI KABUPATEN ACEH TENGAH DENGAN METODE ANALYTICAL HIERARCHY PROCESS (AHP) - Cut Rachmy; Sofyan Sofyan; Irwan Irwan (Program Studi Agribisnis, Fakultas Pertanian, Universitas Syiah Kuala, 2023)
Abstrak:Tembakau(Nicotiana tabacum)merupakansalahsatukomoditaspertanianyangmemilikiperananpenting,tidakhanyasebagaisumberpendapatanbagiparapetani,tetapijugabaginegara.TembakaumerupakansalahsatutanamanyangsedangdikembangkanolehPemerintahKabupatenAceh TengahdenganmelihatpotensipertanianyangadadiKabupatenAceh Tengah. SalahsatudaerahpengembangantembakaudiKabupatenAceh TengahadalahKecamatanBintang.Namun,produksitembakaudiKecamatanBintangbelumberkembangluasdanjumlahproduksiyangmasihterbatassehinggaadanyakesenjanganantarapengembanganproduksitanamantembakaudanproduktivitastanamantembakau.PenelitianinibertujuanuntukmerumuskanstrategialternatifprioritasyangdigunakanuntukstrategipengembanganagribisnistembakaudiKecamatanBintangKabupatenAceh Tengah. Data yangdigunakanpadapenelitianinimenggunakandata primer dansekunder. Data primerdidapatmelaluiwawancaradanobservasi.Sedangkan,datasekundermeliputidata-data yangdiperolehdariinstansiterkait,literatur,laporandancatatanyangberkaitandenganpenelitianini.PendekatanpenelitianyangdigunakanadalahAHPdengansoftwaremicrosoftexcelsebagaialatpengolahandata. HasilpenelitianmenunjukkanbahwabahwastrategiprioritasdalampengembanganagribisnistembakaudiKecamatanBintangKabupatenAceh Tengahadalahstrategiperluasanaksespermodalan.Tobacco Agribusiness Development Strategy in Central Aceh Regency using Analytical Hierarchy Process (AHP) MethodAbstract :Tobacco (Nicotiana tabacum) is an agricultural commodity that has an important role, not only as a source of income for farmers, but also for the country. Tobacco is one of the crops that is being developed by the Central Aceh District Government by looking at the agricultural potential that exists in Central Aceh District. One of the tobacco development areas in Central Aceh District isKecamatanBintang. However, tobacco production in Bintang Sub-district has not developed widely and the amount of production is still limited so that there is a gap between the development of tobacco plant production and tobacco plant productivity. This study aims to formulate priority alternative strategies used for the development strategy of tobacco agribusiness in Bintang District, Central Aceh Regency. The data used in this study used primary and secondary data. Primary data was obtained through interviews and observations. Meanwhile, secondary data includes data obtained from related agencies, literature, reports and records related to this research. The research approach used is AHP with Microsoft Excel software as a data processing tool. The results showed that the priority strategy in the development of tobacco agribusiness in Bintang District, Central Aceh Regency is the strategy of expanding access to capital.